Efecto de la nicotinamida como inhibidor de la poli (ADP-ribosa) polimerasa en cáncer de mama deficiente de BRCA1 - Domínguez Gómez, María Guadalupe Isabel (Universidad Autónoma Metropolitana, 2014)
Introduction: The nuclear enzyme poly (ADP-ribose) polymerase-1 (PARP-1) is essential for the repair of single-strand breaks in DNA by means of base excision repair and represents an important target in the therapy cancer. Inhibitors of PARP-1 have been shown to potentiate the cytotoxic effects of ionizing radiation and chemotherapeutic agents such as carboplatin that DNA damaging or inhibitors topoisomerase I. Nicotinamide has been described as an inhibitor of PARP-1 in vitro, and the vast majority of PARP inhibitors are based on their chemical structure. Results in vitro and in vivo and clinical trials recently, suggest that PARP inhibitors can be used as sensitizers to chemotherapy or radiotherapy as well as monotherapy, killing specifically cancer cells with defective in repair mechanisms DNA, particularly those cancers with mutations in the genes encoding proteins BRCA1 and BRCA2. In this experimental strategy has been called "synthetic lethality". In this study we analyzed the effect of nicotinamide in cancer cells proficient and deficient BRCA1. Methods: The effect of the nicotinamide as an inhibitor of PARP-1 was determined by activity assays in vitro PARP-1 and MDA-MB-436 cells. This effect was verified by immunofluorescence in mammary carcinoma cells treated with nicotinamide in the presence of DNA damage. Subsequently, we analyzed the effect of nicotinamide in combination with cisplatin in cell viability assays in MDA-MB-436 (BRCA1-deficient), MDA MB-231 (BRCA1-proficient) and MCF-7 (BRCA1, low levels of expression) cancer cells. Finally, we analyze the effect of nicotinamide as radiosensitizer by clonogenic assays. Results: our results demonstrated that nicotinamide inhibits PARP-1 activity in vitro and in MDA-MB-436 mammary carcinoma BRCA1-deficient. This effect was also observed in breast cancer cells in the presence of DNA damage. Later demonstrated that nicotinamide decreases viability of MDA-MB-436, MDA-MB-231 and MCF-7. Analysis of the data by the isobologram method showed that the combination of nicotinamide and cisplatin produced a synergistic antiproliferative effect in MDA-MB-436 and MCF-7 cancer cells. Finally we observed that the nicotinamide also sensitizes MDA-MB436 and MDA-MB-231 cancer cells to ionizing radiation. Discussion: these results suggesting that nicotinamide sensitizes cancer cells cisplatin treatment and that this effect is influenced by the status of BRCA1, however in MDA-MB-231 cells should take into account other genetic factors as the status triple negative of cell line. On the other hand, the response to treatment with nicotinamide y ionizing radiation in MCF-7 cells could be associated to deficiency of caspase 3, because it has been reported an increase resistance to ionizing radiation in cancer cells deficient in caspase 3. Conclusion: we results suggest that nicotinamide may be used with sensitizer to chemotherapy and radiotherapy in breast cancer more selectively in BRCA1 deficient BRCA1 cancer cells. Interestingly, these results also suggest that inhibition of PARP-1 by nicotinamide may be favoring synthetic lethality in breast cancer cells.; Introducción: La enzima nuclear poli (ADP-ribosa) polimerasa-1 (PARP-1) es esencial para la reparación de rupturas de cadena sencilla del ADN por la vía de reparación por escisión de bases y representa un blanco importante en la terapia contra el cáncer. Los Inhibidores de PARP-1 han demostrado potenciar los efectos citotóxicos de la radiación ionizante y de agentes quimioterapéuticos como el carboplatino que dañan el ADN o inhibidores de la topoisomeraqsa I. La nicotinamida se ha descrito como un inhibidor de PARP-1 in vitro, y la gran mayoría de los inhibidores de PARP -1 se basan en su estructura química. Resultados in vitro e in vivo y más recientemente de ensayos clínicos, sugieren que los inhibidores de PARP-1 pueden ser usados tanto como sensibilizadores de quimioterapia o radioterapia así como en monoterapia, ocasionando la muerte específicamente en células tumorales con defectos en los mecanismos de reparación del ADN, en particular, aquellos tipos de cáncer con mutaciones en los genes que codifican las proteínas BRCA1 y BRCA2. A esta estrategia experimental se le ha denominado “letalidad sintética”. En este estudio analizamos el efecto de la nicotinamida en células de carcinoma mamario proficientes y deficientes de BRCA1. Metodologías: El efecto de la nicotinamida como inhibidor de PARP-1 fue determinado mediante un ensayo de actividad de PARP-1 in vitro y posteriormente en células MDA-MB-436. Este efecto se comprobó mediante inmunofluorescencia en células de carcinoma mamario tratadas con nicotinamida en presencia de daño al ADN. Posteriormente, analizamos el efecto de la nicotinamida y su combinación con cisplatino mediante ensayos de viabilidad celular en las líneas MDA-MB-436, MDA MB-231 y MCF-7 de carcinoma mamario. Cada una con diferentes estados de BRCA1. Finalmente, analizamos el efecto de nicotinamida como radiosensibilizador mediante ensayos de clonogénicos. Resultados: La nicotinamida inhibe la actividad de PARP-1 in vitro y de PARP-1 endógena en células de cáncer de mama MDA-MB-436 deficientes de BRCA1. Este efecto también fue observado en células de cáncer de mama en presencia de daño al ADN. Posteriormente demostramos que la nicotinamida disminuye la viabilidad de las células MDA-MB-436, MDA-MB-231 y MCF-7. El análisis de sinergismo demostró un efecto se sinérgico con nicotinamida y cisplatino en las células MDA-MB-436 y MCF-7. Finalmente observamos que la nicotinamida sensibiliza significativamente a las células MDA-MB-436 y MDA-MB-231 al tratamiento con radiación ionizante. Discusión: Estos resultados sugieren que la sensibilidad al cisplatino observada en las líneas celulares tratadas con nicotinamida está influenciada por el estado de BRCA1, sin embargo en las células MDA-MB-231 cabe resaltar que existen otros factores genéticos como el estado triple negativo de la línea celular que podrían estar jugando un papel importante. Por otro lado, la respuesta al tratamiento con nicotinamida y radiación ionizante en las células MCF-7 podría estar asociada al estado deficiente de la caspasa 3, debido a que se ha reportado un incremento en la resistencia a la radiación ionizante en células deficientes de caspasa 3. Conclusión: nuestros resultados sugieren que la nicotinamida podría ser utilizada como sensibilizador a la quimioterapia y radioterapia en cáncer de mama y de manera más selectiva en células tumorales deficientes de BRCA1. Interesantemente, estos resultados también podrían sugerir que la inhibición de PARP-1 por nicotinamida podría estar favoreciendo la letalidad sintética en nuestro modelo.